AFM nanoindentation of protein shells, expanding the approach beyond viruses. (January 2018) - Roos, Wouter H.
Graphical abstract: Abstract: The archetypical protein nanoshell is the capsid that surrounds viral genomes. These capsids protect the viral RNA or DNA and function as transport vehicle for their nucleic acid. The material properties of a variety of viral capsids have been probed by Atomic Force Microscopy. In particular nanoindentation measurements revealed the complex mechanics of these shells and the intricate interplay of the capsid with its genomic content. Furthermore, effects of capsid protein mutations, capsid maturation and the effect of environmental changes have been probed. In addition, biological questions have been addressed by AFM nanoindentation of viruses and a direct link between mechanics and infectivity has been revealed. Recently, non-viral protein nanoshells have come under intense scrutiny and now the nanoindentation approach has been expanded to such particles as well. Both natural as well as engineered non-viral protein shells have been probed by this technique. Next to the material properties of viruses, therefor also the mechanics of encapsulins, carboxysomes, vault particles, lumazine synthase and artificial protein nanoshells is discussed here.